2016
DOI: 10.1002/jnr.23862
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in nonhuman primate behavioral development

Abstract: Sex differences in behavior and developmental trajectories in human children are of great interest to researchers in a variety of fields, and a persistent topic of discussion and debate is the relative contribution of biological vs. social influences to such differences. Given the potentially large effects of cultural and social influences on human child development, nonhuman primates are important model species for investigating the biological and evolutionary roots of sex differences in human development. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 95 publications
7
68
0
3
Order By: Relevance
“…Other studies in chimpanzees have shown sex differences in developmental patterns (Lonsdorf, 2017). For example, at Kalinzu, Uganda, immature males showed higher rates of playful object manipulations than immature females (Koops, Furuichi, Hashimoto, & van Schaik, 2015).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies in chimpanzees have shown sex differences in developmental patterns (Lonsdorf, 2017). For example, at Kalinzu, Uganda, immature males showed higher rates of playful object manipulations than immature females (Koops, Furuichi, Hashimoto, & van Schaik, 2015).…”
Section: Introductionmentioning
confidence: 93%
“…One hypothesis is that this difference is the result of sexual selection acting differently on males and females. Indeed,Lonsdorf (2017) argued that "…females are expected to show more behaviours related to offspring care and males are expected to show more behaviours related to competition for mating opportunities". In Sonso, there is no tool or proto-tool use primarily related to offspring care that we are aware of but there are several tool use behaviours related to aggressive displays (i.e.…”
mentioning
confidence: 99%
“…Allerede inden da, i alderen 3-8 måneder, er drengebørn mere interesserede i at kigge på en legetøjsbil end en dukke, mens det er omvendt for piger (Alexander, Wilcox, og Woods 2009). Studier af andre abearter viser også at visse kønsforskelle i adfaerd er biologisk snarere end kulturelt betinget (Lonsdorf 2017). Ligesom hos mennesket opholder drengeaber sig mere vaek fra moren, er mindre sociale og tumler og leger mere vildt end pigeaber, mens pigeaber leger mere foraeldre.…”
Section: Religion Og Tro: Sammenligning Med Andre Landeunclassified
“…In primates, infancy is defined as the period in which the infant is physically depends on the mother to survival. The most commonly used point of reference for determining the end of such a period is the age of nutritional and locomotor weaning (i.e., when the infant is no longer fed on the mother's milk and is no longer carried by the mother) (Lonsdorf, 2017;Pereira & Altmann, 1985). However, within each species' range of behavioral flexibility, the timing and strength of maternal rejection can be quite variable, suggesting that other processes participate in this dynamic (Verderane, 2005).…”
Section: Introductionmentioning
confidence: 99%